Thematic Analysis of Corporate Discourse on Diversity and Inclusion in Organizational Documents - Topalović, Antonio (Oeconomica Jadertina, 2025)
Diversity and inclusion are increasingly integrated into organizational strategies, particularly in the areas of sustainable development, social responsibility, and human resource management. Although these concepts are becoming more prominent in public discourse, it remains insufficiently clear how organizations define and represent them in their official documents. This paper assumes that organizational definitions of diversity and inclusion shape organizational identity and influence the development of management policies and practices. The aim of the study is to examine how these definitions reflect different social, ethical, and managerial orientations and to propose an analytical framework for their classification and interpretation. The research is based on a thematic analysis of organizational documents, through which four functional groups of definitions were identified: motivational–value-based, normative, operational, and declarative. These groups illustrate the different ways organizations conceptualize inclusion, from emphasizing belonging and organizational values, to articulating ethical norms and social responsibility, to operationalizing inclusion through procedures and formal definitions of key concepts. The proposed typology provides a structured framework for understanding discursive approaches to diversity and inclusion and serves as a useful tool for analyzing and evaluating inclusive policies in practice. The findings may support organizations in aligning their stated values with the practical aspects of diversity management and contribute to the development of more coherent and effective inclusion strategies. This further contributes to understanding the role of organizational discourse in shaping inclusive practices and strategies.
Keywords: diversity, inclusion, organizational culture, organizational discourse, management practices, human resources, business ethics